Synthesis of functionalized macrocyclic derivatives of trioxabicyclo[3.3.0]nonadiene - Leber, Sabine; Kollenz, Gert; Wentrup, Curt (Beilstein Journal of Organic Chemistry, 2012)
C72-Macrocyclic systems functionalized with nitroaryl and arylamino groups were synthesized from the bisdioxine diacid dichloride 1,3,5,7-tetra-tert-butyl-2,6,9-trioxabicyclo[3.3.1]nona-3,7-diene-4,8-dicarbonyl dichloride (3).
Keywords: bisdioxine; macrocyclic amines; macrocyclic nitro compounds; tetraoxaadamantane